2017
DOI: 10.1073/pnas.1707645114
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR-Cas9 conformational activation as elucidated from enhanced molecular simulations

Abstract: CRISPR-Cas9 has become a facile genome editing technology, yet the structural and mechanistic features underlying its function are unclear. Here, we perform extensive molecular simulations in an enhanced sampling regime, using a Gaussian-accelerated molecular dynamics (GaMD) methodology, which probes displacements over hundreds of microseconds to milliseconds, to reveal the conformational dynamics of the endonuclease Cas9 during its activation toward catalysis. We disclose the conformational transition of Cas9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
251
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 147 publications
(269 citation statements)
references
References 40 publications
11
251
1
Order By: Relevance
“…Particularly, distances were calculated between the Cα atoms of residues Arg 3.50 and Glu 6. 30 , the center-of-mass (COM) distance between the receptor NPxxY motif and the last 5 residues of the Gα α5 helix, and the COM distance between the Gα (excluding residues in the αN helix) and GÎČ (excluding residues 2-45 in the N-terminus) subunits. Root-mean-square fluctuations (RMSFs) were calculated for the protein residues and ligands, averaged over three independent GaMD simulations and color coded for schematic representation of each complex system (Figure 1).…”
Section: Energetic Reweighting Of Gamd Simulations For Energetic Rewmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, distances were calculated between the Cα atoms of residues Arg 3.50 and Glu 6. 30 , the center-of-mass (COM) distance between the receptor NPxxY motif and the last 5 residues of the Gα α5 helix, and the COM distance between the Gα (excluding residues in the αN helix) and GÎČ (excluding residues 2-45 in the N-terminus) subunits. Root-mean-square fluctuations (RMSFs) were calculated for the protein residues and ligands, averaged over three independent GaMD simulations and color coded for schematic representation of each complex system (Figure 1).…”
Section: Energetic Reweighting Of Gamd Simulations For Energetic Rewmentioning
confidence: 99%
“…b The R3.50-E6.30 distance is the distance between the Cα atoms of conserved residues Arg 3.50 and Glu 6. 30 in the receptors. c The α5 orientation angle is the angle between COMs of the receptor orthosteric pocket, the last 5 and first 5 residues of the Gα α5 helix, illustrated in Figure S8.…”
Section: Notesmentioning
confidence: 99%
“…The HNH nuclease domain of SpCas9 undergoes a substantial conformational rearrangement upon target binding 12–15 , which activates the RuvC nuclease for concerted cleavage of both strands of the DNA 12,16 . It was previously shown that the HNH domain stably docks in its active state with an on-target substrate, but becomes loosely trapped in a catalytically-inactive conformational checkpoint when bound to mismatched targets 10,12 .…”
mentioning
confidence: 99%
“…As demonstrated on the model systems, these implementations facilitate the applications of GaMD in enhanced sampling and free energy calculations of a wide range of biomolecular systems, such as proteins, lipid membrane, nucleic acids, virus particles and cellular complex structures. Ongoing applications of GaMD also include the clustered regularly interspaced short palindromic repeats-CRISPR associated protein 9 (CRISPR-Cas9) system 96 , HIV protease, protein kinases, the acyl carrier proteins, and so on.…”
Section: Discussionmentioning
confidence: 99%